1998
DOI: 10.1002/hep.510270618
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor protects murine hepatocytes from tumor necrosis factor-induced apoptosis in vivo and in vitro

Abstract: Keratinocyte growth factor (KGF) promotes epithelial growth and differentiation and has potent effects on the liver. The coinjection of lipopolysaccharide (LPS) and D-galactosamine (GalN) results in hepatic failure in mice. Mechanistically, LPS-induced tumor necrosis factor (TNF) triggers hepatocyte apoptosis, which is enhanced by GalNarrested transcription. Similarly, the combination of TNF and actinomycin D (ActD) causes hepatocyte apoptosis in vitro. We studied the effect of KGF on LPS and GalNinduced hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…Recent studies have shown an anti-apoptotic effect of KGF on various tissues such as epidermal cells [29], neural cells [30] and hepatocytes [31]. In this study KGF could have exerted such a role on transplanted cells in the early days after transplantation, a time at which some loss of tissue is known to occur [32].…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 72%
“…Recent studies have shown an anti-apoptotic effect of KGF on various tissues such as epidermal cells [29], neural cells [30] and hepatocytes [31]. In this study KGF could have exerted such a role on transplanted cells in the early days after transplantation, a time at which some loss of tissue is known to occur [32].…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 72%
“…12 After wounding, KGF protein and mRNA concentration increases and they are mainly present in the dermal fibroblasts below the wound and at the wound edges, whereas KGF receptor transcripts and also the corresponding protein were exclusively detected in keratinocytes of the epidermis and the hair follicles. 17 These cells migrate over the wound and subsequently proliferate, which leads to complete wound re-epithelization. Conforming to previous experiments, we showed in the present study that the gene transfer of IGF-I cDNA and KGF cDNA individually demonstrated the same effects as previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, KGF stimulates proliferation and exerts an antiapoptotic effect for epithelial cells, which are of major importance for the post-traumatic wound healing. [15][16][17] Another growth factor that was found to be effective in the wound healing process is IGF-I. IGF-I, a protein of 7.7 kDa, is a mesenchymal growth factor that accelerates wound healing by stimulating collagen synthesis and the mitogenicity of fibroblasts and keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, little is known about the function of FGFs in liver homeostasis postnatally, and a role of FGFs in liver repair has not been demonstrated. Since FGF7 is a potent mitogen for hepatocytes in vitro and in vivo (Housley et al, 1994;Strain et al, 1994) and since it can protect hepatocytes from tumor necrosis factor-induced apoptosis (Senaldi et al, 1998), we speculated about a role of FGFs in liver homeostasis and regeneration. To address this question, we chose to express a dominant-negative FGFR mutant in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%